Randomized, double‐blinded, vehicle‐controlled, split‐face study to evaluate the effects of topical application of a Gold Silk Sericin/Niacinamide/Signaline complex on biophysical parameters related to skin ageing. (7th August 2015) - Berardesca, E.; Ardigo, M.; Cameli, N.; Mariano, M.; Agozzino, M.; Matts, P.J.
Synopsis: Objective: To investigate the effects of topical application of a Gold Silk Sericin (GSS) complex on biophysical parameters related to skin ageing. Methods: A range of non‐invasive bioengineering methods were deployed in an 8‐week randomized, double‐blinded, vehicle‐controlled, split‐face study among 40 female subjects aged 40–70. Endpoints measured included expert grades of skin condition, stratum corneum (SC) hydration, SC barrier function, elasticity and surface topography. Results: The GSS complex produced significant single‐variable ( P < 0.05) improvements in SC hydration, barrier function, elasticity and surface topography compared with the Vehicle control. Conclusion: The GSS complex examined in this study represents an interesting new cosmetic topical technology with which to address multiple aspects of aged/photoaged female facial skin.